2019
DOI: 10.3390/nano9091204
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dermal Delivery of Cyclosporine A Loaded in Solid Lipid Nanoparticles

Abstract: Cyclosporine A (CsA) is an immunosuppressant frequently used in the therapy of autoimmune disorders, including skin-related diseases. Aiming towards topical delivery, CsA was successfully incorporated into lipid nanoparticles of Lipocire DM and Pluronic F-127 using the hot homogenization method. Two different nanocarriers were optimized: solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) where oleic acid was the liquid lipid. The developed nanoparticles showed mean sizes around 200 nm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…As a result of its immunosuppressive capabilities, this peptide was initially approved to prevent graft rejection in organ transplantation [ 6 , 7 ], but other clinical applications are now employed, such as in psoriasis or in atopic dermatitis treatment. In addition, clinical trials for the treatment of other types of diseases such as rheumatoid arthritis, ulcerative colitis, or ophthalmic applications are currently under investigation [ 8 , 9 , 10 , 11 , 12 ]. CsA was initially marketed as an oil-based formulation for oral administration (Sandimmune Neoral ® from Novartis); however, nowadays, other commercial formulations of CsA are available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its immunosuppressive capabilities, this peptide was initially approved to prevent graft rejection in organ transplantation [ 6 , 7 ], but other clinical applications are now employed, such as in psoriasis or in atopic dermatitis treatment. In addition, clinical trials for the treatment of other types of diseases such as rheumatoid arthritis, ulcerative colitis, or ophthalmic applications are currently under investigation [ 8 , 9 , 10 , 11 , 12 ]. CsA was initially marketed as an oil-based formulation for oral administration (Sandimmune Neoral ® from Novartis); however, nowadays, other commercial formulations of CsA are available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing Figure 5, it is possible to observe biocompatibility and safety of SLNs up to concentrations of 6 mg mL −1 in lipid for both cell lines, corresponding to a CsA concentration of approximately 0.6 mg mL −1 . In previous studies performed by the group, free CsA was toxic for L929 when using concentrations higher than 35 µg mL −1 and for HaCaT using concentrations higher than 17.5 µg mL −1 [38]. For the higher tested lipid concentrations (8 and 10 mg mL −1 ) containing 0.8 and 1 mg mL −1 in CsA, respectively, cell viability decreased to values below 70%, indicating a cytotoxic effect that was more evident in keratinocytes ( Figure 5B) than in fibroblasts ( Figure 5A), when compared to the control cells.…”
Section: Cell Viabilitymentioning
confidence: 87%
“…The mean size, polydispersity index (PDI) and zeta potential of the formulations were determined using a ZetaPALS zeta potential analyzer (Brookhaven Instruments Corporation; Holtsville, NY, USA) [38]. Samples where diluted in double deionized water (1:100), which is the same aqueous phase used to prepare the nanoparticles prior each determination.…”
Section: Average Size and Surface Potential Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, an in vivo experiment showed that cytokines levels of IL-4 and IL-5, normally overexpressed in atopic dermatitis, decreased by 40% in both cases [ 138 ]. Topical CyA delivery was also achieved by Silva and colleagues (2020) [ 140 ], Essaghraoui and co-workers (2019) [ 139 ], and Trombino and collaborators (2020) [ 141 ]. Efficient permeation was observed with reduced transdermal permeation.…”
Section: Nlc Containing Natural Substances Against Skin Inflammationmentioning
confidence: 97%